2008
DOI: 10.1111/j.1745-3933.2008.00495.x
|View full text |Cite
|
Sign up to set email alerts
|

The radial alignment of dark matter subhaloes: from simulations to observations

Abstract: We explore the radial alignment of subhaloes in two‐dimensional projections of cosmological simulations. While most other recent studies focused on quantifying the signal utilizing the full three‐dimensional spatial information any comparison to observational data has to be done in projection along random lines‐of‐sight. We have a suite of well‐resolved host dark matter haloes at our disposal ranging from 6 × 1014 to 6 × 1013 h−1 M⊙. For these host systems, we do observe that the major axis of the projected tw… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
18
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 44 publications
10
18
0
Order By: Relevance
“…7 are too large to detect a radius dependence in the position angle distributions. We note again however, that our observed radial alignments are much weaker than that found for the alignments of haloes in N -body simulations (Knebe et al 2008b). Our observed mean position angles are consistent at 2-σ with previous measurements using SDSS isophotal shapes (Pereira & Kuhn 2005;Faltenbacher et al 2007), which found equivalent values of φ ∼42-44 • with φ increasing with increasing group radius.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…7 are too large to detect a radius dependence in the position angle distributions. We note again however, that our observed radial alignments are much weaker than that found for the alignments of haloes in N -body simulations (Knebe et al 2008b). Our observed mean position angles are consistent at 2-σ with previous measurements using SDSS isophotal shapes (Pereira & Kuhn 2005;Faltenbacher et al 2007), which found equivalent values of φ ∼42-44 • with φ increasing with increasing group radius.…”
Section: Resultssupporting
confidence: 87%
“…Kuhlen et al (2007) and Knebe et al (2008b) showed that using only the inner 10-20% of the particles in a dark matter sub-halo, rather than all bound sub-halo particles, introduces significant scatter in the distribution of radial alignment angles that is more consistent with previous observations. Using N -body simulations with gas and star formation physics included, Knebe et al (2010) concluded that gas physics does not measurably affect the radial alignment angles of satellite galaxies relative to the orientations inferred from studying the parent dark matter sub-haloes alone.…”
supporting
confidence: 78%
“…Furthermore, it has also been reported in the literature that the orientation of their shapes is not random and their major axis preferentially points towards their host centre (e.g. Kuhlen et al 2007; Faltenbacher et al 2008; Knebe et al 2008a,b; Pereira et al 2008). This ‘radial alignment’ is quantified by the (cosine of the) angle between the position vector of the subhalo d sat in the rest frame of its host halo and the major axis a sat of the actual subhalo (again, as determined via the eigenvectors of the standard moment of inertia tensor).…”
Section: Resultsmentioning
confidence: 92%
“…Agustsson & Brainerd 2006;Kang et al 2007;Faltenbacher et al 2008;Knebe et al 2008;Okumura et al 2008). Since real galaxies are seen in projection, we project the dark matter distribution before diagonalizing the moment of inertia tensor.…”
Section: The Orientations Of Semi-analytic Galaxiesmentioning
confidence: 99%